A Jurisprudential Study of the Hadith "There is No Vow for a Person in What They Do Not Possess, No Redemption in What They Do Not Possess, and No Divorce in What They Do Not Possess": A Hadith-Fiqh Study - Alomari, Mohammad Ahamad Mohammad; Al Momani , Israa Mousa Jaffal; Alomari , Randa Abedelkarim Abdealhafiz (Dirasat: Shari’a and Law Sciences, 2023)
Objectives: This research examines the Hadith of Amr ibn Shuayb, focusing on the statement that "there is no vow, redemption, or divorce in what a person does not possess." The study delves into hadith and fiqh sciences, assesses scholars’ opinions on its authenticity, and explores associated fiqh issues. Additionally, the research aims to elucidate jurists’ viewpoints and evidence, striving to determine the most accurate stance on the matter. Methods: The study followed an analytical methodology through a hadith study based on the chain of narrations, methods, evidence, and fiqh issues contained in the hadith. The study also adopted an inductive approach by deducing the opinions of critical scholars in judging the authenticity of the hadith, determining its degree of authenticity, and deducing the fiqh choices in fiqh issues related to the hadith. Results: The study concluded that the hadith has multiple chains of narrations and evidence, and is considered one of the accepted hadiths that have an authentic chain of narrations and text. The study also concluded that the hadith is the main source of evidence for the consensus of scholars that there is no vow, redemption, or divorce in what a person does not possess, due to the strength and clarity of the evidence. Conclusions: The study confirms the authenticity of the hadith and its text, and confirms that there are no legal implications or considerations for vows, redemption, or divorce in what a person does not possess. The study recommends the continuation of hadith-fiqh studies related to fiqh issues that affect people’s lives, to understand their legal rulings, and to abide by them according to the Prophet’s guidance.